Impact of Health Education Intervention Program on Breast Self Examination among College Girls of Chitwan, Nepal - Panthi , Srijana; Manandhar, Alisha; Upreti, Arish; Lohani, Suman (Annapurna Journal of Health Sciences, 2025)
Introduction: Breast self-examination (BSE) is a screening method that is cheap, non-complicated, and non-invasive. The purpose of BSE is to become familiar with the way your breasts normally look and feel. Hence, this study was conducted to assess the impact of a health education intervention program on BSE among College students of Chitwan. Methods: A College-based pre-experimental study was done among 90 bachelorlevel students of a government College in Bharatpur Metropolitan of Chitwan District, Nepal. An intervention health education program imparting knowledge was assessed and compared before and after intervention. The results were analyzed by using both descriptive as well as inferential statistics. Results: A total of 90 female College students aged 18-23 years were included in the sample. The level of knowledge of students on BSE has increased significantly post-intervention as compared to pre-intervention. Before intervention 50% had inadequate knowledge and after intervention 97.8% had adequate knowledge. The test of significance revealed that the increment in BSE knowledge score due to program intervention was highly significant (P<0.001). This study also found that there was a difference in the mean pretest awareness score according to women pursuing BBA (p<0.036). Based on the mean score, the score was significantly higher among women who have never performed a breast examination (P<0.020) Conclusion: The knowledge of BSE was observed to be inadequate in respondents but there was a significant improvement after the intervention.